Children's Increased Emotional Egocentricity Compared to Adults Is Mediated by Age‐Related Differences in Conflict Processing. Issue 3 (27th January 2015) - Hoffmann, Ferdinand; Singer, Tania; Steinbeis, Nikolaus
<x xml:space="preserve">Abstract</x> This study investigated the cognitive mechanisms underlying age‐related differences in emotional egocentricity bias (EEB) between children (aged 7–12 years, n = 30) and adults (aged 20–30 years, n = 30) using a novel paradigm of visuogustatory stimulation to induce pleasant and unpleasant emotions. Both children and adults showed an EBB, but that of children was larger. The EEB did not correlate with other measures of egocentricity. Crucially, the developmental differences in EEB were mediated by age‐related changes in conflict processing and not visual perspective taking, response inhibition, or processing speed. This indicates that different types of egocentricity develop independently of one another and that the increased ability to overcome EEB can be explained by age‐related improvements in conflict processing.